Fine tuning of magnetization relaxation parameters of the DyO+ single ion magnet in a hydroxy/fluoro-apatite solid solution. Issue 1 (23rd November 2018) - Kazin, Pavel E.; Zykin, Mikhail A.; Trusov, Lev A.; Vasiliev, Alexander V.; Kolesnik, Irina V.; Schnelle, Walter; Felser, Claudia; Jansen, Martin
Abstract : Variation of the crystal environment of DyO + regulates the energy barrier for magnetization reversal and the rate of quantum tunneling of magnetization. Abstract : DyO + embedded in a hydroxy/fluoro-apatite matrix reveals robust and finely tunable single-ion-magnet properties. The energy barrier for magnetization reversal grows with the increase in the fluoride and Dy content. A high Dy concentration slows down the quantum tunneling of magnetization, contrary to a commonly observed trend for its acceleration.